Hversu algeng er langvinn lungnateppa? : íslensk faraldsfræðirannsókn - Bryndís Benediktsdóttir; Gunnar Guðmundsson; Kristín Bára Jörundsdóttir; William Vollmer; Þórarinn Gíslason (Læknafélag Íslands, Læknafélag Reykjavíkur, 2007)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn View/Open OBJECTIVE: To investigate the prevalence of chronic obstructive pulmonary disease (COPD) in Iceland and possible risk factors. MATERIALS AND METHODS: This Icelandic survey is a part of an international study (www.BOLDCOPD.org). The target population consisted of a simple random sample taken among all non-institutionalized Icelanders 40 years and older living in Reykjavik and adjacent suburbs (n=938). Participants were subjected to a structured interview based on questionnaires on respiratory diseases, symptoms, life style and possible risk factors. They also underwent a spirometry that was repeated after inhalation of a bronchodilating agent. COPD stage I, or higher, was defined according to the GOLD staging (www.goldcopd.org) based on chronic airflow limitation (FEV1/FVC 70%) persisting after inhaled bronchodilator. RESULTS: Full participation was by 755 (80.5%). Altogether 18.0 % of the participants fulfilled criteria for COPD, GOLD stage I or higher and 9.0 % for GOLD stage II or higher. There were proportionally more young females (40-49 years) than males diagnosed with COPD GOLD stage I or higher (8.1% compared to 4.8%), even though there was no difference in total prevalence between males and females. The prevalence of COPD increased with increasing age and the amount of tobacco smoked. Only a part of those fulfilling criteria for COPD had been diagnosed by doctors. CONCLUSION: Our results show a high prevalence of COPD among Icelanders 40 years and older when internationally accepted criteria and methods are used. These results are useful for heath authorities when planning and giving priority in our future health care system. Tilgangur: Markmið rannsóknarinnar var að kanna algengi og mögulega áhrifaþætti langvinnrar lungnateppu meðal Íslendinga á höfuðborgarsvæðinu. Efniviður og aðferðir: Um er að ræða hluta af fjölþjóðarannsókn (www.BOLDCOPD.org) þar sem val á efnivið og aðferðir eru staðlaðar. ...